2001
DOI: 10.1046/j.1524-475x.2001.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen in wound healing: More than a nutrient

Abstract: Abstract. This article provides an overview of the role of oxygen in wound healing. The understanding of this role has undergone a major evolution from its long-recognized importance as an essential factor for oxidative metabolism, to its recognition as an important cell signal interacting with growth factors and other signals to regulate signal transduction pathways. Our laboratory has been engaged in thestudy of animal models of skin ischemia to explore in vivo the impact of hypoxia as well as the use of oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…This capability of fibroblasts is unusual, at least among mesenchymally derived cells, and appears to be important in normal development, wound healing, and fibrosis as well as in the vascular changes that characterize hypoxic pulmonary hypertension (1)(2)(3). With regard to pulmonary artery adventitial fibroblasts, we have shown that among the resident vascular wall cells they exhibit the earliest and most dramatic responses to hypoxic exposure in vivo (4).…”
mentioning
confidence: 82%
“…This capability of fibroblasts is unusual, at least among mesenchymally derived cells, and appears to be important in normal development, wound healing, and fibrosis as well as in the vascular changes that characterize hypoxic pulmonary hypertension (1)(2)(3). With regard to pulmonary artery adventitial fibroblasts, we have shown that among the resident vascular wall cells they exhibit the earliest and most dramatic responses to hypoxic exposure in vivo (4).…”
mentioning
confidence: 82%
“…However, severe hypoxia in diabetic wounds often fails to directly trigger effective angiogenesis because of significant cell death under such conditions. In fact, hyperbaric oxygen treatment is beneficial for wound healing in diabetic foot ulcers [216], presumably by rescuing cells in wounded tissues from hypoxia-induced death. Rather interestingly, only intermittent hyperbaric treatment is beneficial, whereas continuous hyperbaric treatment is toxic and prevents wound healing [216].…”
Section: Hypoxia and Pathological Angiogenesismentioning
confidence: 99%
“…In fact, hyperbaric oxygen treatment is beneficial for wound healing in diabetic foot ulcers [216], presumably by rescuing cells in wounded tissues from hypoxia-induced death. Rather interestingly, only intermittent hyperbaric treatment is beneficial, whereas continuous hyperbaric treatment is toxic and prevents wound healing [216]. A likely cause to the toxicity may be the generation of reactive oxygen species, but down-regulation of HIF-a levels under hyperoxia may also diminish the expression of angiogenic factors.…”
Section: Hypoxia and Pathological Angiogenesismentioning
confidence: 99%
“…(7) There is no doubt that other mechanisms are also involved, including nerve transmission control, algeassic substance reduction and control of the inflammatory response and associated irritative substance release, but as a simple and easily demonstrated effect, enhanced superficial blood flow was shown following LLLT in injured sumo wrestlers. With the enhancement of superficial blood flow, there will narturally be an increase in the oxygen tension values, and the importance of the role of oxygen in initiating and sustaining wound healing has recently become even more apparent than before, (8,9) and the oxygen gradient into injured areas, along which reparative cells migrate, has been measured. (10) …”
Section: Discussionmentioning
confidence: 99%